Hegemoni Kelas Berkuasa dalam Naskah Drama Kidung Senyap Seorang Perempuan Karya Ikhwan Setiawan - Sri Wahyuni; Agus Setiawan; Suci Ayu Latifah (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
The purpose of this study is to reveal the hegemony of the ruling class in the drama script Kidung Senyap Seorang Perempuan by Ikhwan Setiawan. The hegemony of the ruling class is one of the areas of study of Gramsci's hegemony theory. The theme of power is always exotic to study, interesting to explore, put forward, and actualized throughout human life. The issue of power will give birth to the ruling classes—which at first are neutral but on the way they turn, take sides. In the analysis, the researcher uses Antonio Gramsci's theory of hegemony as a knife to the hegemony of the ruling class. This research method uses descriptive qualitative. The object of the research is the drama script of Kidung Senyap Seorang Perempuan by Ikhwan Setiawan. Based on the results of the analysis, the hegemony of the ruling class is born in various forms, including: i) getting rid of those who disagree, (ii) oppression of the lower classes, (iii) physical and psychological violence, (iv) sexual harassment, and (v) making unilateral regulations.